Evaluation of food literacy in young elite athletes - Stephanie Mosler and Maximilian von Lippe-Falkenflucht and Petra Lührmann and Anja Carlsohn (Abstractband zum ... wissenschaftlichen Kongress, 2019)
Objective: In competitive sports, nutritional intake must be adapted to the demands of different competitive phases to ensure adequate intake. Therefore, the ability to organize one’s everyday nutrition in a self-determined, responsible and en-joyable way (food literacy) is required. So far, little is known about food literacy in young elite athletes (YEA) and about strategies to strengthen their food literacy. Aim of this study was to evaluate different components of food literacy in YEA: nutrition knowledge, meal planning, selection of individually adequate food and cooking skills.Methods: Nutrition knowledge, food shopping habits, meal planning and cooking skills were assessed in 114 YEA (15.5 ± 1.8 yr, 55 f/59 m) from Elite School of Sports and the Olympic Sports Centre in Stuttgart/Germany using a pilot-tested, reli-able questionnaire.Results: All athletes (100 %) consider a healthy and individually adequate nutrition important for health and physical perfor-mance. However, 81 % of them point out to have difficulties to choose a healthy sports nutrition in everyday life. In particular, lack of time (52 %) is mentioned. Although only 4 % of YEA consider inadequate nutritional knowledge as an obstacle for healthy sports nutrition, in our test 88 % actually show little nutritional knowledge (3 ± 1 of 9 points). Only 22 % of YEA habitually plan to purchase food or meal preparation. 46 % are not confident in meal preparation without using convenience products. When preparing meals 27 % never use vegetables, 11 % never use potatoes, rice or noodles, whereas 58 % always use meat.Conclusion: Our results indicate that time pressure, lack of nutritional knowledge and poor skills in meal preparation may be a challenge for YEA to follow a healthy diet that meets the requirements of their sports activity. Educational programs that support athletes in nutrition knowledge, food preparation and individual time management skills as part of food literacy may promote healthy eating in this group.